Citraan dalam Novel di Kaki Bukit Cibalak Karya Ahmad Tohari : Kajian Stilistika - Soenandar Pritojosoa; Juanda Juanda; Faisal Faisal (HUMAN: South Asian Journal of Social Studies, 2022)
Abstract. This study aims to describe the types of imagery contained in the novel Di Kaki Bukit Cibalak by Ahmad Tohari and the function of the images found using a stylistic approach. The data in this study are excerpts of text, sentences, and paragraphs in the novel Di Kaki Bukit Cibalak by Ahmad Tohari. The data source in this research is the novel Di Kaki Bukit Cibalak by Ahmad Tohari published by PT Gramedia with the fourth printing in June 2014 in Jakarta. The data in this study were studied in depth using a stylistic study according to Burhan Nurgiyantoro. Data collection techniques in this study were carried out by reading and note-taking techniques. Furthermore, the data is processed into identifying data, classifying data, analyzing and validating data. The results of this study indicate that there are five types of imagery used by Ahmad Tohari as a novelist. There are 319 image data which are divided into; 158 visual imagery data (visual), 33 auditory imagery data (auditive), 108 motion image data (kinesthetic), 13 tactile thermal imagery data and 7 olfactory imagery data. From this image data, the researcher found that there was an image function that influenced the storyline in the novel. The function of this image is then categorized into three main functions, namely the function of clarifying the image, enlivening the image in the mind and senses, and the function of generating a special atmosphere. Keywords: Stylistics, Novels, Imagery, Ahmad Tohari.